The Role Of The Coach In Creating Positive Trends Towards Sitting Volleyball - Field Study Of Teams Of The First National Division In The Algerian Federation For Disabled Sport - - Amine, Ait Mouheb; Ahmed, Yakhlef (Journal of Sport Science Technology and Physical Activities, 2021)
The study aims to determine the role of the sitting volleyball coach in forming positive trends towards the sitting volleyball. a descriptive method was used to suit the nature of the study. This was indicated by a sample of 60 randomly selected players. The researcher used the trainer's survey and the trend survey. We collected the data using spss19. After collecting and processing the results, we concluded that a coach has a role in forming positive trends towards sitting volleyball On this basis, the study recommended helping the group of persons with disabilities to practice sitting volleyball, and form training centers for trainers in order to develop and promote the sport of the handicapped nationally and internationally.